Economic globalisation and economic justice: Covenanting for action between the Reformed churches of South Africa and Germany - Damon, Malcolm (HTS teologiese studies, 2009)
The premise of this article is that ethical moral formation or ‘covenanting for justice’ leads to action. The covenanting church itself, in conjunction with other movements, works for justice in all areas of life. The article uses the six aspects of ethical moral formation of Heinz Tödt to analyse some aspects of economic globalisation in order to form moral judgements that will lead to joint action. These six aspects are: assessing the problem as a moral issue; analysing the problem to determine to what extent it challenges the affected; weighing different behavioural responses to the problem; ascertaining what norms, goods and perspectives could play a role in the different moral choices; communicating ethical decisions to stakeholders; and the moral decision and actions themselves.